PERSEPSI PETANI TERHADAP PENGGUNAAN KREDIT USAHA RAKYAT (KUR) DALAM MENINGKATKAN USAHATANI KOPI DI KECAMATAN SIBOLANGIT - Iman Arman; Wahyuni Sipayung; Aisar Novita (Universitas Sebelas Maret, 2024)
Farmer’s Perceptions of the Use of People’s Business Credit (PBC) in Improving Coffee Farming Businesses in Sibolangit District, Deli Serdang Regency. This study aims to examine the level of farmer’s perceptions and examine the factors that influence farmer’s perceptions of the use of People’s Business Credit (PBC) in improving coffee farming. This research was conducted in Sibolangit District, Deli Serdang Regency, from April to June 2023. The data collection methods were interviews, questionnaires tested for validity and reliability, and recording, while the data analysis method used a Likert scale and multiple linear regression. The study results show that the level of farmer’s perception of using People’s Business Credit (PBC) in improving coffee farming is 82.42 percent. Partial further tests using tcount show that the factors of length of farming, income level, role of extension workers, social environment, and PBC socialization have quite a significant influence, with the tcount value being greater than the table.